2022
DOI: 10.1016/j.fsigen.2022.102675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the VISAGE basic tool for appearance and ancestry inference using ForenSeq® chemistry on the MiSeq FGx® system

Abstract: The possibility of providing investigative leads when conventional DNA identification methods fail to solve a case can be of extreme relevance to law enforcement. Therefore, the forensic genetics community has focused research towards the broadened use of DNA, particularly for prediction of appearance traits, bio-geographical ancestry and age. The VISible Attributes through GEnomics (VISAGE) Consortium expanded the use of DNA phenotyping by developing new molecular and statistical tools for appearance, age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Different strategies can be applied for mixture detection with MPS-based biallelic SNP assays. Mixtures can be identified by observing variation in the allele read frequency or by detecting an increase in heterozygotes [ 40 ]. We could successfully distinguish mixtures from single-source samples down to 1:10 mixtures by applying either of the proposed detection methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies can be applied for mixture detection with MPS-based biallelic SNP assays. Mixtures can be identified by observing variation in the allele read frequency or by detecting an increase in heterozygotes [ 40 ]. We could successfully distinguish mixtures from single-source samples down to 1:10 mixtures by applying either of the proposed detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…All mixtures were analyzed in duplicate, with 10 ng DNA as input amount. The ability to detect a mixture was evaluated by investigating the allele read frequency (ARF) distribution and by calculating the heterozygosity rate [ 40 ]. The ARF for each locus was calculated by dividing the read depth of the allele with the most reads with the total number of reads.…”
Section: Methodsmentioning
confidence: 99%
“…The VISAGE ( Vis ible A ttributes Through Ge nomics) Consortium, which consists of 13 partners from academic, police, and justice institutions in 8 European countries, has established new scientific knowledge and developed and tested prototype tools for DNA analysis and statistical interpretation as well as conducted education for stakeholders. In the 2019 to 2022 time window of this review, this concerted effort produced 45 one review article [ 417 ], 22 original research publications [ 337 , [420] , [421] , [422] , [423] , [424] , [425] , [426] , [427] , [428] , [429] , [430] , [431] , [432] , [433] , [434] , [435] , [436] , [437] , [438] , [439] , [440] ], and three reports [ [441] , [442] , [443] ].…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…Recently, more researchers have started to apply massively parallel sequencing technologies for ECVs application for both commercial [ 7 , 8 , 9 ] and non-commercial developments [ 10 ]. However, only a few MPS studies concerning forensic DNA phenotyping focused on degraded DNA samples, i.e., DNA samples with poor quality or low quantity of DNA [ 9 , 10 , 11 , 12 , 13 , 14 ] whose analysis often shows partial or inconclusive genetic results.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies [ 9 , 10 , 11 , 12 , 14 ] reported the performance of the MPS assay on a set of forensic samples, different for biological tissue, and artificially degraded samples obtained with sonication treatment. The results showed well-balanced tests suitable for forensic casework by their high sensitivity with full SNP profiles obtained down to 100 pg of DNA input.…”
Section: Introductionmentioning
confidence: 99%